Enhancing User Experience in a Land Transportation Information Application: A Design Thinking Approach to the GOBIS Application - Lisana Lisana; Melissa Angga; Eugenia Caitlyn Cristabella (Journal of Electrical Engineering and Computer (JEECOM), 2026)
GOBIS is a digital transportation application developed by the Surabaya City Government to facilitate public access to public transportation services. As a land transportation information system, GOBIS plays an important role in providing route, bus stop, and fleet information for urban mobility. However, user reviews and usability test results indicate that the current version of the application still has several shortcomings, particularly in interface design and user experience. The main issues include a difficult-to-interpret integrated map, the absence of an automatic route-search feature, and unclear information about bus stops and fleets. This study developed a redesigned GOBIS prototype through the five-stage Design Thinking process and evaluated the existing application and the redesigned prototype using the same task scenarios. Effectiveness was measured by task completion rate, efficiency by time-based efficiency, and perceived user experience by the User Experience Questionnaire (UEQ). The redesigned prototype increased task completion from 52% to 92%, representing a 40-percentage-point improvement, and increased time-based efficiency from 0.008 to 0.104 goals/sec. User satisfaction also improved after the redesign. Furthermore, assessment with the User Experience Questionnaire (UEQ) showed that all dimensions fell within the “excellent” category. These findings indicate that the redesigned interface successfully improves the overall quality of user interaction and enhances the user experience of GOBIS as a land transportation information system.